TGfU in the teaching of handball at school: impacts on the motor coordination and technique in the game - Tatiane Mazzardo; Schelyne Ribas; Pablo Juan Greco; Gabriella Nelli Monteiro; Willian José Bordin da Silva; Nayanne Dias Araújo; Layla Maria Campos Aburachid (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: This study investigated the impact of a handball-teaching program through the understanding of the TGfU on motor coordination (MC) and technical skills of students. Methods: The sample consisted of 43 students of both genders, with a mean age of 14.3 years (± 0.46), divided into two groups, G1 - Teaching Games of Understanding (TGfU) and G2 - TGfU + MC, and both received 20 classes. We used the Körperkoordinationstest für Kinder (KTK) for the assessment of MC and the Game Performance Assessment Instrument (GPAI) for technical skills in handball. Results: The categorization confirmed the reliability of the application of teaching programs and the results showed that, after the intervention, both groups presented meaningful improvements in MC, considering time and gender effect. The female students presented a larger impact on MC in both teaching programs, while the male students obtained a larger impact in the technical skill execution index when received the TGfU + MC model. Still, the relative frequency for the classification of a good MC increased in both groups after the intervention, and the normal MC was the one with the highest frequency in both groups and genders after the proposed program. Conclusion: We concluded that the teaching program was able to provide meaningful improvements in MC considering both groups and that the proposal of the inclusion of specific MC elevated the impact of technical skills for male students.